Challenges in data management in the agri-food industry. A systematic comparison of permissioned blockchain-based IT business applications - Mónica Martínez-Casta\~neda; Claudio Feijoo (International Telecommunications Society (ITS), 2023)
This article includes a bibliographic study to identify, evaluate, and interpret existing research regarding the effectiveness of blockchain technology applications in the field of agricultural production condition accreditation. Drawing from the review, and to illustrate the technical architecture of the blockchain-based logistics tracking system, the article focuses on the management of raw data as a system parameter that will determine the advantages and limitations of existing business solutions. Additionally, considerations are incorporated into the system construction to reduce information asymmetry and increase the business power of producers when using public databases. Basically, the bibliographic compilation and analysis are aimed at improving two aspects: the veracity and relevance of the production data collected in the blockchain systems, and offering tentative handling methods that increase the producers' power of control over the systems by using data and verifications already completed for the administration for other purposes.
Keywords: 330